UJI SERBUK DAUN BINAHONG (Anredera cardivolia) DALAM PAKAN TERHADAP KINERJA PERTUMBUHAN UDANG VANAME (Litopenaeus vannamei) - Anis Zubaidah; Dony Prasetyo; Novia Budii Lestari (Universitas Muhammadiyah Malang, 2024)
Vaname shrimp (Litopenaeus vannamei) is a fishery commodity that has economic value. Vaname shrimp demand from year to year continues to increase. Increasing shrimp demand can be surmounted by accelerating shrimp growth. The purpose of this study was to know the best dose which most effective of binahong leaves powder in feed on the growth performance of vaname shrimp. Shrimp used are sized 5-6 grams. This study uses a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications to obtain 15 experimental units. In the control treatment without Binahong leaf powder, treatment 1 (10 grams/kg feed), treatment 2 (20 grams/kg feed), treatment 3 (30 grams/kg feed), and treatment 4 (40 grams/kg feed). The parameters measured are ADG / daily growth, absolute length growth, BWG / body weight gain, Mean Body Weight (MBW), survival rate, amount of feed consumption, feed efficiency, Feed Conversion Rate (FCR), and moulting frequency. The results of the study showed that the addition of Binahong leaf powder in feed significant effect (P<0,05) on the ADG / daily growth, absolute length growth, BWG / body weight gain, and feed efficiency, but not significcant effect on the Mean Body Weight (MBW), survival rate, amount of feed consumption, Feed Conversion Rate (FCR), and moulting frequency. The best results are obtained on the treatment 3 (30 grams/kg feed) with the value of ADG / daily growth harian 0,72 grams, absolute length growth 2,75 cm, BWG / body weight gain 92%, Mean Body Weight (MBW) 8,36 grams, survival rate 97,76%, FCR 1,24 grams, amount of feed consumption 113,43 grams, feed efficiency 42,33 grams and moulting frequency 18 shrimps